Comparison of motor relearning occupation-based and neurodevelopmental treatment approaches in treating patients with traumatic brain injury - Nowa, Jackson (My University, 2020)
Background: Traumatic Brain Injury is caused by trauma related to motor vehicle accidents (MVAs), accidental falls and violence. Around the world, approximately 69 million people annually suffer a traumatic brain injury due to various causes with the majority of cases affecting low and middle income countries (LMICs). The management of traumatic brain injury requires a multidisciplinary approach which includes rehabilitation. The main aim of the study was therefore to evaluate the outcomes of the Neurodevelopmental Treatment) and motor relearning occupation-based approaches on physical performance and self-care among adults with traumatic brain injuries. Methods: An experimental research design comparing two groups and a pre-test post-test design was used in the study. No control group was included as all participants with traumatic brain injury were receiving treatment using either of the two approaches. The researcher developed a demographic questionnaire to determine demographic characteristics of the study, the Fugl Meyer Assessment to evaluate the motor performance and a Modified Barthel Index to ascertain the functional independence of the participants before and after interventions. Results: Forty (66.7%) participants were male with ages ranging from 18 to 68 years, half (50%) had secondary education, about 35% had tertiary education and the majority (50%) were never married. Almost all (98.3%) the participants had no previous history of injury with only one reporting a previous traumatic brain injury. Motor vehicle accidents accounted for the majority of participants’(65%) injury with an age range of 18 –54. A Wilcoxon Signed Rank Test revealed a statistically significant increase in Fugl Meyer and Modified Barthel Index values for all aspects of the assessment following participation in the motor relearning occupation-based group and the Neurodevelopmental Treatment group in the upper and lower extremity values, (p< 0.001) with large effect sizes. A Mann Whitney U test revealed that motor relearning occupation-based approaches were more effective than the Neurodevelopmental Treatment approaches with most components for both groups achieving the reported minimal clinically important difference. There was a significant statistical difference in total scores for the motor relearning approach and the Neurodevelopmental Treatment group, (p = 0.020, with a large effect size (r=0.42)), upper extremity (p = 0.014) and wrist scores (p = 0.027) with large effect sizes (r=0.45) and (r=0.40) respectively indicating the difference was clinically important. Mann Whitney U test, applied to compare post-test Modified Barthel Index scores revealed a significant difference in the chair/bed transfer in motor relearning occupation-based group participants and had a significantly larger improvement in mobility components including chair/bed transfers (p = 0.002), ambulation (p = 0.037), stair climbing (p = 0.027) and toilet transfers (p = 0.023) all with large and moderate effect sizes (r=0.28-0.39). There was an improvement on self-care components including bathing (p=0.001), dressing (p=0.001) and personal hygiene (p=0.008) with large effect sizes (r=0.34-0.53), indicating clinically important improvement compared to Neurodevelopmental Treatment group participants. There was no significant difference in ambulation, bowel and bladder control and feeding between motor relearning occupation-based and Neurodevelopmental Treatment approach group participants with small effect sizes. The Neurodevelopmental Treatment approach showed greater improvement in pain scores on a Fugl Meyer upper extremity test and lower extremity test. Conclusion: Both the motor relearning occupation-based and the Neurodevelopmental Treatment approach are effective in improving physical performance and self-care after acute traumatic brain injury with significant changes within both groups for all components assessed. The motor relearning occupation-based approach showed greater improvement in the total, upper extremity and wrist scores as reported by the Fugl Meyer upper extremity test. It also showed superiority in the Modified Barthel index scores namely chair/bed transfers, ambulation/wheelchairs/ stair climbing, toilet transfers and bathing, dressing and personal hygiene
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy, 2020